A genome-wide association study of late-onset Alzheimer's disease in a Japanese population. (August 2015) - Hirano, Atsushi; Ohara, Tomoyuki; Takahashi, Atsushi; Aoki, Masayuki; Fuyuno, Yuta; Ashikawa, Kyota; Morihara, Takashi; Takeda, Masatoshi; Kamino, Kouzin; Oshima, Etsuko; Okahisa, Yuko; Shibata, Nobuto; et al.
Abstract : Objective: Although a number of genome-wide association studies (GWASs) of late-onset Alzheimer's disease (LOAD) have been carried out, there have been little GWAS data on East Asian populations. Design: To discover the novel susceptibility loci of LOAD, we carried out a GWAS using 816 LOAD cases and 7992 controls with a replication analysis using an independent panel of 1011 LOAD cases and 7212 controls in a Japanese population. In addition, we carried out a stratified analysis by APOE -ε4 status to eliminate the established effect of APOE region. Results: Our data indicated that 18p11.32 (rs1992269, P =9.77×10 −7 ), CNTNAP2 (rs802571, P =1.26×10 −6 ), and 12q24.23 (rs11613092, P =6.85×10 −6 ) were suggestive loci for susceptibility to LOAD. Conclusion: We identified three suggestive loci for susceptibility to LOAD in a Japanese population. Among these, rs802571, located at intron 1 of CNTNAP2, was considered to be a plausible candidate locus from a functional perspective. Abstract : Supplemental Digital Content is available in the text.